Determinants of maize farmers' performance in Benin, West Africa - Amegnaglo, C.J. (Elsevier B.V., 2018)
Increased agricultural productivity is the primary aim of all agricultural policies undertaken in developing countries. Increased agricultural productivity involves not only the analysis of factors limiting productivity but also efficiency because improved efficiency leads to productivity improvement. This paper investigated the factors limiting maize productivity in Benin based on a survey of 354 maize farmers. The mean maize yield was 1,347 kg/ha. The low level of maize yield in Benin is due to the lack of access to inputs, capital, and the weak institutional environment in which farmers operate. Furthermore, the efficiency model revealed that an increase in maize output of about 25 percent can be achieved in the short run by adopting the best farming practices and by addressing socioeconomic and structural constraints. Policy should be encouraged that would facilitate access to inputs, capital, and training, and promote the development of infrastructure in farming areas.
Journal Article
Keywords: Benin; maize; production constrains; stochastic frontier analysis; yield analysis